Bioactive Compounds in Lipid Fractions of Pumpkin (Cucurbita sp) Seeds for Use in Food - Veronezi, Carolina Medici [UNESP]; Jorge, Neuza [UNESP] (Wiley-Blackwell, 2012)
Seeds are considered to be agro-industrial residues, which can be used as source of macronutrients and/or raw material for extraction of vegetable oils, since they present great quantities of bioactive compounds. This study aimed to characterize the lipid fractions and the seeds of pumpkin (Cucurbita sp) varieties Nova Caravela, Mini Paulista, Menina Brasileira, and Moranga de Mesa aiming at using them in food. The chemical composition of the seeds was performed according to the official methods of American Oil Chemists' Society and Association of Official Analytical Chemists. Total carotenoids and phenolic compounds were determined by spectrophotometry, while the levels of tocopherols were analyzed by high efficiency liquid chromatography. It was noted that the seeds contain high amounts of macronutrients that are essential for the functioning of the human organism. As to total carotenoids, Mini Paulista and Menina Brasileira pumpkin varieties presented significant amounts, 26.80 and 26.03 mu g/g, respectively. Mini Paulista and Nova Caravela pumpkin varieties showed high amounts of total phenolic compounds in the lipid fractions and in the seeds. It was also found that gamma-tocopherol is the isomer that stood out in the lipid fractions and in the seeds, mainly in Menina Brasileira. Finally, the consumption of these seeds and use of lipid fractions provide the supply of large quantities of compounds that are beneficial for health and that may be potentially used in food, besides representing an alternative to better use of agro-industrial residues.
Keywords: Carotenoids; Cucurbitaceae; macronutrients; Phenolic compounds; Tocopherols